TI_GERICHTE 90.2008.8 vom 7. September 2009 , Conferma dell'attribuzione alla zona agricola di alcuni fondi - TI Tribunale d'appello (2009)
Conferma dell'attribuzione alla zona agricola di alcuni fondi